2003
DOI: 10.1007/s00198-003-1490-4
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after osteoporotic fractures

Abstract: The aim of this study was to examine the pattern of mortality following osteoporotic fractures at the spine, shoulder, hip, and forearm. We studied 2,847 patients with fractures at these sites identified from the radiology department in Malmö, Sweden. Poisson regression was used to compute mortality immediately after the fracture and with time. Mortality immediately after fracture was significantly higher in fracture cases than in the general population except for forearm fractures in both men and women. Morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
445
7
32

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 742 publications
(523 citation statements)
references
References 20 publications
39
445
7
32
Order By: Relevance
“…Many patients with osteoporotic hip fractures have previously been found to be undernourished and suffering from proteinenergy malnutrition (PEM) (Ponzer et al, 1999). Osteoporosis is also a predictor of mortality (Johnell et al, 2004) and, likewise, the MNA has been found to predict mortality in geriatric patients both during short-term stays in the hospital (Van Nes et al, 2001) and during a long-term 3-year followup (Persson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with osteoporotic hip fractures have previously been found to be undernourished and suffering from proteinenergy malnutrition (PEM) (Ponzer et al, 1999). Osteoporosis is also a predictor of mortality (Johnell et al, 2004) and, likewise, the MNA has been found to predict mortality in geriatric patients both during short-term stays in the hospital (Van Nes et al, 2001) and during a long-term 3-year followup (Persson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have shown that in postmenopausal women the consequences of vertebral fractures are markedly influenced by the number and severity of prior vertebral fractures [7,27]. It has been reported that patients with multiple fractures are at increased risk of morbidity and mortality [2,14]. Therefore, the recognition of vertebral fractures is critical for the prediction of possible future fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that wrist fractures are associated with some costs and quality of life reductions the first year after fracture [23][24][25][26]. Wrist fractures have not been indicated to increase mortality compared to the general population [27][28][29]. The incidence of fracture increases linearly with age (see Figure 1).…”
Section: Diagnosis Epidemiology and Pathologymentioning
confidence: 99%
“…Hip and vertebral mortality rates in the first and following years after fracture event were derived from different published sources [27,128,130], respectively. In the raloxifene, study a relative risk of mortality after clinical vertebral fractures estimated at 2.5 the year after fracture and 1.3 in subsequent years for all ages was used.…”
Section: Epidemiological Datamentioning
confidence: 99%